USOS DE OPERADORES ARGUMENTATIVOS E DIVERSIFICAÇÃO DOS TIPOS DE ARGUMENTOS EM TEXTOS DE ALUNOS DO 9º ANO - ELIANA RIBEIRO DA SILVA MENEGUSSI (2021)
Concerning the teaching of mother tongue in Brazilian schools’ panorama, in the recent decades, the assumption of the text as the basis for the Portuguese language classes stands out, a fact that can be seen in the BNCC (2018), (National Common Curricular Base). This latter document maintains as the centrality of the textual genres study, so that, the student can reflect on the functioning of language in different situations of use in reading and text production activities, highlighting, in the textual unit, all other aspects related to language, such as sounds, lexicon, syntactical structures, etc. A written activity requires a wide range of knowledge, linguistic strategies and procedures that directly affect the construction of meanings. In view of this, this research is based on the theorical assumptions of Textual Linguistics, following, above all, Marcushi (2012), Koch (2000) and Fávero (2002). Its general objective is to propose a Activity Sequence (AS) aimed at expanding the argumentative written competence of 9th grade students and, as specific objectives, to bring activities that combine two knowledges: argumentative operators and types of argument, treated with greater depth and thus provide diversified opportunities for students to have richer experiences with the language at work. Another specific objective is to combine each proposed activity with the potentially developed skills, highlighting this relationship, which is so necessary for the teacher's work. For a more consistent proposition with the reality of the classroom, a group of students from a state public school, from Aspásia-SP, was used as a reference. To achieve this goal, the genre opinion article was used, focusing on the meanings and functions of the argumentative operators, linguistic expedients that are essential for the organization of the parts and the chain of ideas. With a greater command of the argumentative operators, it is believed that it is also possible to invest in the diversification of the types of arguments used and connecting these two contents is one of the specific objectives of the research. It is worth mentioning that, in addition to the observation of student productions, the materials made available to the school on the subject were also the object of reflection. In an analysis of the São Paulo state Curriculum, from which the didactic materials “Student’s Notebook” and “Teacher’s Notebook” come from, we can see the need to expand the target contents to improve the coherence and cohesion in the textual productions of the students at this school year. Thus, the methodology of this work was to observe opinion articles written by 9th grade students, and then to elaborate a list of sequenced activities, with the respective theoretical bases that support them and the procedures to be adopted by the teacher. For the theoretical and methodological basis of the proposal, we assume the affirmations of Dolz, Noverraz, Schneuwly (2011), proponents of the Didactic Sequence (DS), which in the state of São Paulo is adapted to Activity Sequence (AS). It is expected that the proposition elaborated about the argumentative operators and the types of argument, required knowledge for the construction of the opinion article, will be a possibility for future applications in the classroom and, by extension, a possible contribution for the improvement of the students writing competence.